Population dynamics of the Taimyr reindeer population - Pavlov, B.M.; Kolpashchikov, L.A.; Zyryanov, V.A. (Rangifer, 1996)
The Taimyr herd of wild reindeer (Rangifer tarandus tarandus L.) is one of the three largest herds of wild Rangifer in the world, and numbered about 600 000 in 1993. The herd grew continuously from 1959 to 1990, and is now stable due primarily to intensive commercial harvesting along the Khatanga River. Meat from the commercial harvest is processed and sold in population centers in the northern Krasnoyarsk region, particularly Norilsk. The herd has expanded its range to about 1.5 million km2, but movements to the southwestern portion of the winter range may have been impeded by pipeline, road and railroad construction, and winter shipping of ore on the lower Yenisey River.